Tracer particle motion driven by vortex formation in the bottom boundary layer underneath internal solitary waves - Ellevold, Thea Josefine; Grue, John; Sletten, Joakim Soløy (Frontiers in Marine Science, 2023)
Internal solitary waves (ISWs) of large amplitude moving in the coastal ocean induce sizeable horizontal velocities above the sea bed. In turn, these give rise to instability and vortex formation in the bottom boundary layer (BBL), and sediment resuspension and concentration maintenance in the water column. We present two-dimensional laminar simulations in a numerical tank suitable for internal wave motion, including the processes of the BBL. The combined wave and vorticity field encounters a cloud of tracer particles near the bottom. The tracer particles are moved vertically because of the vorticity field during a first encounter. The reflected wave intercepts a second time with the tracer particles, which are then moved further vertically. Numerical experiments with a kinematic viscosity of 1/100 cm2 s−1 or 1/1000 cm2 s-1 are used to manipulate the scale of the Reynolds number at a moderate and great laboratory scale. The final vertical position of the tracer particles is found below a vertical level of approximately 0.23 times the water depth (H) after the second passage. The result is independent of the scale. This vertical position matches available field measurements of a summer benthic nepheloid layer reaching a height of 0.19H. The laminar model predictions compare very well to the ISW-driven vortex formation measured in a three-dimensional laboratory wave tank. Convergence of the calculated vortex formation is documented.